Comparative analysis of environmental, social and governance (ESG) ratings: do sectors and regions differ? - Pillai, Rekha (2024)
Sustainable and holistic investment philosophy such as environmental, social and governance (ESG) concepts have now emerged as the subtle, comprehensive and concrete response to the unprecedented surge in environmental, social and financial market sustainable development problems. The main aim of this paper is to perform an in-depth study on ESG ratings world-wide and to granularly analyse how and why they differ within industries and regions as reported by Sustainalytics on 13,589 companies as of December 2022. Perceiving ESG ratings from dual dimensions, we introduce the ‘push–pull effect’ where we identify the rationale pushing corporates for providing their ESG engagements to ESG rating providers and the justification for stakeholders pulling information from these rating providers. Correspondence analysis, nonparametric independent sample Kruskal–Wallis test and Mann–Whit ney test are performed as tools of inference. Results reveal that Asia and America are regions demonstrating high ESG risks with European corporates exhibiting low ESG risks. In terms of industry, transportation infrastructure and media, both categorized under low ESG risk, portray a statistically significant difference from other industries. Finally, the sector wise reports clearly evince an overall statistically significant difference between financial and non-financial sector in all regions, the former presenting high risk ESG scores in Asia and North America. Policy implica tions are set as ESG is a concept which has stepped out of the “awareness creation” stage to an implementation state, imploring policy makers to embark on stringent measures of ensuring ESG compliance to reap stakeholder confidence and ensure sustainable development.